Endeavour towards sustainability: an empirical study of an Indian electronics retail industry. (4th February 2022) - Joshi, Deepika
This exploratory study seeks to examine the reverse supply chain as a source of sustainability in retail firms of India. The determinants of sustainability are discerned using data collected from 302 consumer electronics retailers. The findings reveal that at retailer's level, sustainability is embedded in planning for reverse collection process, monitoring the information, dealing with uncertainties, supply chain responsiveness for productivity and decision making at strategic level. The reverse supply chain strategies implemented by Indian electronic retailers is a distinctive contribution of the presented research. The retailers practice different approaches to achieve benefits of their eco-friendly strategies. But certain institutional and structural constraints limit their intent. Such concerns are highlighted and viable solutions are suggested for immediate industry practice.